Masyarakat utama : konsepsi dan strategi - Yusuf, M. Yunan, 1949- (Jakarta : Perkasa, 1995)
Islamic community development in Indonesia, Islam and politics; papers of a seminar
Diterbitkan oleh Perkasa dengan bekerjasama dengan Lembaga Pengkajian dan Pengembangan PP Muhammadiyah
Includes bibliographical references
Keywords: Islam -- Social aspects -- Indonesia; Islam -- Social aspects; Islam and politics -- Indonesia